Experimental determination of safe service life of motorcycle helmet - Hamzah, Azhar (2016)
The most distressing trauma in motorcycle crashes is head injury which has caused over 50% of motorcyclist death. Such rate stresses the importance of an effective protective equipment, the motorcycle safety helmet. Helmet protects by reducing the impact forces from reaching the users’ heads upon impact contact. New helmets performance is well assured, however, after a certain period of use, their performance may deteriorate to less than optimum due to environmental and use factors such as ultraviolet exposures and unintentional drops/impacts. There is scarce information on the impact performance of used helmet. This performance is usually measured by headform acceleration in laboratory test. This study attempts to determine used helmet impact performance with regards to headform acceleration performance in impact test. It intends to determine used helmet headform acceleration performance relative to service age, examine headform acceleration performance at critical side and identify factors affecting used helmet headform acceleration performance. The study involves performing impact test in an established test facility, SIRIM QAS, Shah Alam. It utilises the Malaysian helmet standards protocol, MS1:1996, as the basis for conducting experiment and acquiring the headform acceleration values. In brief, 65 helmet samples were collected randomly near Kajang and Semenyih townships. These helmet varies in service ages and in a number of physical attributes such as shell and liner thickness, though all were certified to the same test standards when new. 10 of 65 helmets (15.4%) were not tested due to failure in complying with the fit-for test criteria. 55 helmets were impact tested at four sides per helmet (front, right, left and rear) and the variables studied were headform acceleration, service age, helmet mass, shell thickness, liner thickness and density, impact speed and impact energy. Two different impact severities were adopted, impact velocities of 6.4 m/s onto a flat anvil and 5.8 m/s onto an hemispherical anvil. Helmets were randomly numbered and during test, the test order was systematically change to minimize bias. The test result indicated the helmets have a wide spectrum of service ages, from 6 months to 167 months with a mean of 65 months. It reveals the retention pattern of helmet in the nearby townships. In addition, almost all helmets were capable of meeting the headform acceleration limit (≤300g) at different impact severities, despite all the conditions they may have gone through during use tenure. The key reason for the positively high pass to fail rate (96.4%) was possibly the filtering process of helmet samples which had basically removed a substantial number of helmets not fit-for-test (15.4%). Statistically, there were significant correlations of helmet headform acceleration to the service age, helmet mass, liner thickness, shell thickness and impact energy (p<0.05). There was no significant different of impact performance between the four impact sides (p>0.05). Helmet deterioration measurement was not quantified due to lack of baseline information. The samples make and model were not identifiable in many cases and the certification information is confidential. The study also attempts to model headform acceleration with the assumption that the relationships between all independent variables (service age, helmet mass, shell thickness and liner thickness) and dependent variable (headform acceleration) was linear. Comparison of two aged helmets, 27 and 37 months showed that the prediction for higher impact energy (111J) was relatively closed to the actual test result (around 5%), however for lower impact energy (96J), the variation exceeds 18%. The linear assumption has limit the model applicability to a service age range of 24 months. Moreover, the small sample size of helmets (N=55) may not allow any deduction of conclusive evidence for any generalisation. A strict filtering process to qualify helmet for impact test may have removed important data and should be reconsidered in future work for more representative and conclusive information. In short, the study has presented meaningful information on used motorcycle helmet impact performances relative to headform acceleration and associated factors. It has also established introductory data on helmet retention and performance pattern for motorcyclists.